Evaluation of potential reaction between BaZr0.8Y0.2O3-δ ceramics and Pt at high temperatures. Issue 17 (1st December 2019) - Xu, Yangsen; Kou, Hongning; Fang, Shuohai; Wang, Xianfen; Bi, Lei
Abstract: BaZr0.8 Y0.2 O3-δ (BZY20) is found to react with Pt at high temperatures, although Pt is generally regarded as an inert material that prevents its reaction with many materials even at high temperatures. The reaction between BZY20 with Pt is difficult to be confirmed by X-ray diffraction (XRD) analysis as no observable secondary phase can be detected even after high-temperature treatment. However, the obvious color change of the fired BZY20 powder implies the potential reaction. Therefore, transmission electron microscopy-energy dispersive X-ray spectroscopy (TEM-EDS) and X-ray photoelectron spectroscopy (XPS) techniques are used to have an insightful analysis of the material. TEM-EDS result indicates that there is an existence of Pt element in the BZY20 powder after firing, suggesting a Pt diffusion into the BZY20 lattice. XPS analysis results further confirm the content of Pt 4+ and Pt 2+ in the BZY20 powder after firing and the content of Pt 4+ increases with the increase of firing temperatures, and the increase of Pt 4+ content lowers the O1s binding energy, which might be beneficial for the proton migration.